Adverse pro-tumorigenic effects of IDO1 catalytic inhibitors mediated by the non-enzymatic function of IDO1 in tumor cells - Rossini, Sofia; Ambrosino, Sara; Volpi, Claudia; Suvieri, Chiara; Pallotta, Maria Teresa; Belladonna, Maria Laura; Sorcini, Daniele; Macchiarulo, Antonio; Hennes, Elisabeth; Ziegler, Slava; Waldmann, Herbert; Orabona, Ciriana (Frontiers in Immunology, 2025)
Indoleamine 2,3-dioxygenase 1 (IDO1) inhibitors have been developed with the aim of reinvigorating antitumor T-cell responses in the tumor microenvironment by blocking the conversion of the essential amino acid tryptophan into immunoregulatory kynurenines. The lack of efficacy demonstrated in the clinical trials prompts us to revise the “on-target” mechanism of these molecules. By studying the turnover of IDO1 protein in human tumor cells exposed to various IDO1 catalytic inhibitors, such as epacadostat, linrodostat, and navoximod, we show here that these molecules stabilize a non-enzymatic protein conformation of IDO1, independently of their mechanism of inhibition. In the thyroid carcinoma cell line FTC-133, the stabilized and non-enzymatic IDO1 protein promotes the proliferation and migration of the tumor, resulting in an adverse pro-tumorigenic effect. These results uncover an unexpected adverse effect of IDO1 inhibitors in the tumor microenvironment that overcomes the enzymatic inhibition of IDO1, and suggest protein degradation, rather than enzymatic inhibition, as a more effective approach to target IDO1 in the tumor microenvironment.